Elimination of safety nonconformities in a mining company using Lean Manufacturing tools - Alves, Lionel; Pereira, Natália Fernanda Santos; Rosa, Germano Mendes; Policarpo, Renata Veloso Santos (Brazilian Journal of Production Engineering, 2024)
This article presents how the implementation of Lean Manufacturing tools was carried out in a mining company located in the Alto do Paraopeba basin. The aim of the work was to eliminate safety non-compliances identified through weekly rounds. The initial idea of these rounds was carried out applying the concepts of Lean Manufacturing using the tool called Kamishibai, in addition to this tool, two others were used: 5S and Kaizen. The challenge encountered when carrying out the work was changing the culture in the sector in which the study was applied, since the majority of non-conformities that were found are situations that are present in the daily lives of employees. The purpose of applying these tools was also to increase leadership involvement with the Gemba (factory floor), making it possible to provide better working conditions for employees. Furthermore, through the tools applied, the sector's culture improved, promoting greater team involvement and satisfaction as the environment became safer.
Keywords: Safety; Mining; Lean manufacturing